Energy transition or energy diversification? Critical thoughts from Argentina and Brazil. (December 2022) - Lampis, Andrea; Ibañez Martín, María María; Zabaloy, María Florencia; Schirmer Soares, Raiana; Guzowski, Carina; Mandai, Silvia Sayuri; Lazaro, Lira Luz Benites; Hermsdorff, Sonia Maria G.L.; Bermann, Célio
Abstract: This paper aims to analyze the implications of the energy transition policies in Argentina and Brazil. The paper's goal is to illustrate that the two countries are undergoing a transformation of their energy systems toward greater diversification of the energy supply and probably, not a socially inclusive one. Based on data on national energy policies, the evolution of the energy supply mixes over the period 1990–2020, and access to electricity by the households at the national level, the paper offers a critical reading of how the two countries faced the challenges posed by the present process of energy system transformation. The paper adopts a political economy and political ecology perspective employing the notion of just energy transition (JET) to illustrate the contradictions and tensions of the latter approach analyzing quantitative data related to the transformation of the energy system and energy poverty in both Argentina and Brazil. Highlights: Argentina and Brazil reflect a trend towards an energy transformation rather than a transition. Both countries present a modest incidence of solar and wind installed capacity. The incidence of energy poverty in Argentina is 17% and 9.9% in Brazil. Strengthening energy communities is a core policy challenge in both countries.